(untitled) (Bangladesh Journal of Botany, 2023)
Polyethylene terephthalate (PET) is a polymer used in the production of water and beverage bottles as well as textiles, and packaging materials. The aim of this study is to isolate and characterize PET-associated bacteria. The samples were collected from different sites in Dhaka and inoculated into enriched culture media. The predominant bacteria were Bacillus (31%), Pseudomonas (31%), and Enterobacter (10%), while others were Listeria, Enterobacter, Citrobacter, Klebsiella, Kluyerea, Staphylococcus and Morganella. Most bacteria can grow at 30 - 40°C temperature and 6.5 - 7.5 pH. Bangladesh J. Bot. 52(4): 1071-1076, 2023 (December)